1999
DOI: 10.1080/00071669987935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium bentonite on the performance and blood variables of broiler chickens intoxicated with aflatoxins

Abstract: 1. This study was conducted to evaluate the protective effect of natural sodium bentonite (NaB) in the prevention of toxic effects of aflatoxins. Five hundred and twenty-eight 1-d-old Ross male broiler chickens were housed in pens (22 chickens per pen) for 42 d. There were 3 inclusion rates of NaB (0, 2.5, and 5 g/kg) and 2 of aflatoxins (0 and 3 mg/kg food). Each treatment had 4 replicates of 22 chickens. 2. All chickens treated with aflatoxin and without bentonite were adversely affected. NaB treatment at 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 15 publications
6
47
1
9
Order By: Relevance
“…Ocorreu diminuição significativa, nas concentrações séricas de P dos animais tratados com aflatoxina e 0,5% de montmorilonita sódica (Tabela 2), o que concorda com Santurio et al (1999), que observaram redução de 30% das concentrações séricas de P, em razão da inclusão do adsorvente. Eraslan et al (2005) consideram que esta diminuição resulta da alta capacidade adsorvente da bentonita sódica (montmorilonita sódica), que pode adsorver também Ca e P, não só a aflatoxina, no trato gastrintestinal.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Ocorreu diminuição significativa, nas concentrações séricas de P dos animais tratados com aflatoxina e 0,5% de montmorilonita sódica (Tabela 2), o que concorda com Santurio et al (1999), que observaram redução de 30% das concentrações séricas de P, em razão da inclusão do adsorvente. Eraslan et al (2005) consideram que esta diminuição resulta da alta capacidade adsorvente da bentonita sódica (montmorilonita sódica), que pode adsorver também Ca e P, não só a aflatoxina, no trato gastrintestinal.…”
Section: Resultsunclassified
“…Esse adsorvente só evitou a diminuição sérica de ácido úrico, quando foi administrado na concentração de 0,5%, o que está de acordo com Santurio et al (1999) e Batina et al (2005), que utilizaram o mesmo adsorvente, em frangos de corte intoxicados por aflatoxina na dieta, e concluíram que a adição de montmorilonita sódica, nesta concentração, é capaz de prevenir os efeitos da aflatoxicose.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Tauqir et al (2001) and Santurio et al (1999) reported that poultry performance was improved with the use of silicate minerals in broiler diets. In turkeys, body weight gain and feed conversion ratio (FCR) significantly improved with dietary Si dioxide supplementation (Tran et al 2015).…”
Section: Introductionmentioning
confidence: 99%